Uji Kelarutan Si Tersedia pada Trass Bakar dan Non Bakar: Experiment of Silica Solubility Availabilityon Fuel and Non Fuel Trass - Mirawanty Amin; Budi Nugroho; Dyah Tjahyandari Suryaningtyas (Departemen Ilmu Tanah dan Sumberdaya Lahan, Fakultas Pertanian, IPB University, 2019)
This research was conducted to determine the available Si between burned trass and unburned trass, also to determine the best formula to be used as silica fertilizer. This research was conducted at the Laboratory of Soil Chemistry and Fertility, Department of Soil Science and Land Resources, Faculty of Agriculture, IPB University. The experimental design was the split-plot with the main plot consisted of burned trass and unburned trass, and the subplot consisted of combination dosage of trass and CaCO3, those were 100% trass, 83.33% trass + 16.67 CaCO3, 66.67.% trass + 33.33% CaCO3, each treatment was replicated three times, resulting in 18 experiment units. The result showed that the burned trass showed the highest available Si compared to the unburned trass. The combination of 83% trass + 17% CaCO3 showed the highest available Si of those were 120.02 ppm, 72.67 ppm and 53.43 ppm, respectively with extractant of ammonium acetate pH 4.8, 0.5 M HCl and H2O. Keywords: